Effect of flour polymeric proteins on dough thermal properties and breadmaking characteristics for hard red spring wheat genotypes. (March 2016) - Simsek, Senay; Ohm, Jae-Bom; Cariou, Vincent; Mergoum, Mohamed
Abstract: The aim of this research was to investigate the effect of variation of flour polymeric proteins on dough thermal properties for hard red spring (HRS) wheat genotypes grown in the U.S. state of North Dakota. Flour polymeric proteins were analyzed by size exclusion HPLC for sodium dodecyl sulfate (SDS) buffer extractable and unextractable fractions. Mixolab was employed to measure dough thermal property. The Mixolab torque profile was fitted to nonlinear equations, and envelope amplitude value was calculated by treating the torque profile as a wave. The dough tolerance to thermal weakening, as determined from the Mixolab parameters (including the constants of a nonlinear model and envelope torque amplitude values derived from the mixing torque profile during heating from 30 to 70 °C), was identified to have significant (P < 0.05) and positive correlations with flour bread loaf volume potential. Variations of high molecular weight polymeric proteins appeared to affect dough tolerance to thermal weakening and bread loaf volume for HRS wheat genotypes, and different associations with breadmaking characteristics were observed according to extractability in SDS buffer. Negative correlations with tolerance to thermal weakening and bread loaf volume were seen for SDS extractable polymeric proteins and positive correlations were observed for unextractable polymeric proteins. Highlights: This research investigated the effect of variation of flour polymeric proteins on dough thermal property for hard red spring wheat. Dough tolerance to thermal weakening was identified to have positive correlations with flour bread loaf volume potential. High molecular weight polymeric proteins appeared to affect dough tolerance to thermal weakening and bread making property.